Hydrodynamic calculation of wedge-shaped system «slider-guide» operating on compressible lubricant in presence of melt on surface of guide - K. S. Akhverdiev; E. A. Bolgovа; E. O. Lagunova; S. V. Kumanin (Омский научный вестник)
In the article on the basis of the equation of motion of the compressible lubricant for the «thin layer», continuity, state, and the equation describing the profile of the molten contour taking into account the formula of mechanical energy dissipation the asymptotic and self-similar solution is found for the extreme (when the speed tends to infinity) and non-extreme case. As a result of solving the problem, a refined mathematical calculation model of a wedgeshaped sliding support with a low-melting metal coating on a movable contact surface is obtained, which compensates for an emergency lack of lubricant and provides a stable hydrodynamic lubrication mode.